Structure and binding properties of Pangolin-CoV spike glycoprotein inform the evolution of SARS-CoV-2 - Antoni G. Wrobel (Nature Portfolio, 2021)
It has been suggested that pangolin coronaviruses may be the origin of SARS-CoV-2. Here the authors show that the Pangolin-CoV spike is structurally closely related to the closed form of SARS-CoV-2 spike and exhibits similar binding properties to human and pangolin ACE2; although neither spike binds bat ACE2.